EVALUASI KINERJA LAYANAN PERPUSTAKAAN UIN SUNAN AMPEL SURABAYA BERBASIS STANDAR NASIONAL DAN INTERNASIONAL - Rodliyah, Ummi (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2022)
The performance of the university library must always be evaluated and assessed. Assessment or evaluation activities usually have to use standard measuring tools, so that the results can be accounted for. The results of the evaluation carried out correctly can be used as a reference and basis for library development in the future. This research is an evaluated study of the library service performance evaluation of UIN Sunan Ampel Surabaya (UINSA). The standards used as evaluation tools are the National Standards for College Libraries (SNP 13 of 2017) and the Standards for libraries in higher education issued by the Association of College and Research Libraries (ACRL), a division of the American Library Association (ALA). 2018. Using both instruments of national and international standards, the researcher wants to know the level of achievement of UINSA's library service performance from these two levels. This study uses the collecting data methods, namely documentation, questionnaires, and observations. Documentation is used to evaluate performance based on SNP 13 in 2017 while a questionnaire is used to evaluate performance based on the Standard for libraries in higher education. Documentation guide using the university library accreditation instrument. Meanwhile, the questionnaire was compiled based on the performance indicators of the 3 (three) principles of Standard for libraries in higher education, namely Professional Values, Education role, and Discovery. The results showed that the performance of UINSA Library services based on SNP 13 of 2017 had reached the standard, with a value of 4.6. The Evaluation based on the Standard for libraries in higher education, it also exceeds the standard with a value of 4.2. The results of this study became the basis for the preparation of a long-term library development policy document as part of the quality manual document. A document that will form the basis of library development for the next 5 years.